Коловратки (Rotatoria) жаберной полости длиннопалого речного рака бассейна Днепра. Сообщение II - Бошко, Е.Г. (Вестник зоологии, 1980)
The fauna of Rotatoria, specific symbionts of the Astacidae gill cavity (Lepadella astacicola, L. lata, L. branchicola, L. raja, L. nаnа and Dicranophorus hauerianus) is characterized qualitatively and quantitatively. Seasonal dynamics of their quantity is shown under conditions of the Dnieper basin water bodies. Besides Rotatoria species confined to Astacidae representatives of the Rotatoria, Cephalodella, Lecane and others who usually lead a free mode of life were found in the Astacidae gill cavity. It is stated that during ecdysis of Astacidae there are no rotifers in their cavity.